TEACHING ENGLISH FOR JUNIOR HIGH SCHOOL THROUGH CONTEXTUALTEACHING AND LEARNING (CTL) METHOD - Roberto W Marpaung (Proceeding of International Conference on Art, Language, and Culture, 2017)
This research was aimed to prove that the application of contextual teaching and learning method can be used in teaching English especially to increase vocabulary mastery of the students in junior high school. This research applied true experimental research design involving two groups; experimental and control group. The researcher used random sampling technique to determine the sample of the research. The seventh year students at SMP Negeri 19 Palu were selected as the sample of the research. The instruments of the data collection were tests given to the research sample consisting of pre-test and post-test. The data gathered were analyzed statistically. The result of the research showed that the t- counted (9.091) was greater than the t- table (1.999) by applying 0.05 level of significance and the degree of freedom (df) was 62. It meant that the application of contextual teaching and learning method can significantly increase the vocabulary mastery of the seventh year students at SMP Negeri 19 Palu. In conclusion, contextual teaching and learning method can be used to teach English especially to increase the students’ vocabulary mastery.